Feasibility and Mechanism Analysis of Shenfu Injection in the Treatment of Idiopathic Pulmonary Fibrosis - Liu, Peipei; Yang, Shengnan; Wang, Zai; Dai, Huaping; Wang, Chen (Frontiers in Pharmacology, 2021)
Background: Idiopathic pulmonary fibrosis (IPF) is disease with high mortality, and its effective treatment is limited. Shenfu injection is a traditional Chinese medicine which can improve circulation and protect cells. In this study, we aimed to investigate the feasibility and mechanism of Shenfu injection in the treatment of IPF. Methods: The components and targets of Shenfu injection were mainly retrieved from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) database. The targets of Shenfu injection were standardized by UniProt database. The Genecards and OMIM databases was used to search for IPF-related genes. The Venn diagram of gene intersection was drawn using the OmicStudio tools, and the protein-protein interaction network was visualized using the Cytoscape 3.7.2 software. Moreover, the metascape online software was applied to explore the enriched Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and the Cytoscape 3.7.2 software was used to construct the target-pathway network. Molecular docking was used to visualize the interactions between the main active compounds and targeted proteins. Animal experiments were performed to validate the effects and mechanisms of Shenfu injection. Results: We obtained 46 co-targets of Shenfu injection and IPF. Among the hub target genes, several genes with important functions were enriched, including TNF, IL-6, IL-1B, TP53, JUN, CASP3 and CASP8. The pathway enrichment analysis for the hub target genes identified pathways in infection/inflammation, apoptosis and cancer. Molecular docking results showed that the main active compound Ginsenoside Re had high affinity to the core target proteins. These results suggested that Shenfu injection may have a positive effect in the treatment of IPF. Consistent with this finding, animal experiments showed that Shenfu injection significantly reduced pulmonary fibrosis in a mouse model with inhibition of apoptosis and inflammation by downregulating IL-1β, caspase-3 and phosphorylated NF-κB. Conclusion: Our results demonstrated that Shenfu injection efficiently alleviate bleomycin-induced pulmonary fibrosis through multi-targets in inflammation-, apoptosis- and cancer-related pathways, which provided first evidence and reference to the feasibility of Shenfu injection in the treatment of IPF.